Austrolebias reicherti Loureiro & García, a valid species of annual fish (Cyprinodontiformes: Rivulidae) from Uruguay - Loureiro, Marcelo; García, Graciela (Zootaxa, 2008)
This article analyzes the available morphological (morphometric, meristic, and coloration patterns) and molecular evidence that supports the taxonomic validity of Austrolebias reicherti. The species can be differentiated from A. charrua Costa & Cheffe, recently proposed as a senior synonym (Costa 2006), by the following combination of characters (characters of A. charrua in parenthesis): 1) origin of dorsal fin anterior to that of the anal fin (origin of dorsal fin posterior to that of the anal fin), 2) 18 to 24 caudal fin rays (23–26), 3) black supraorbital band well developed (moderately developed), 4) a vertical band present on the posterior borders of dorsal and anal fins (band absent), 5) base of dorsal fin banded and anal fin uniformly pigmented (both fins dotted at least on their proximal section), and 6) vertical dark bands on body flank narrower or equal in width to the lighter space between bands (vertical bands equal or wider than space between bands). According to morphological and molecular data, it is also concluded that A. salviai Costa, Litz & Laurino is a junior synonym of A. reicherti.